Understanding Another Person's Emotions—An Interdisciplinary Research Approach - Juckel, Georg; Heinisch, Christine; Welpinghus, Anna; Brüne, Martin (Frontiers in Psychiatry, 2018)
An interdisciplinary research perspective is developed concerning the question of how we understand others’ emotions and how reliable our judgment about others’ emotion can be. After an outline of the theoretical background of emotions, we briefly discuss the importance of prior experiences and context information for the recognition of emotions. To clarify this role, we describe a study design, utilizing emotional expressions and context information while controlling for prior experiences and the actual emotional situation to systematically approach these questions.